Report from the 26th Meeting on Toxinology, “Bioengineering of Toxins”, Organized by the French Society of Toxinology (SFET) and Held in Paris, France, 4–5 December 2019 - Pascale Marchot; Sylvie Diochot; Michel R. Popoff; Evelyne Benoit (Toxins, 2020)
This 26th edition of the annual Meeting on Toxinology (RT26) of the SFET (http://sfet.asso.fr/international) was held at the Institut Pasteur of Paris on 4−5 December 2019 [...]